Experiments and modeling for thermal conductivity of graphite nanoplatelets/carbon composites. Issue 12 (1st December 2016) - Yue, Qi; Jin, Shuangling; Guo, Chenting; Gao, Qian; Zhang, Rui; Jin, Minglin
ABSTRACT: In this work, the graphite nanoplatelets/carbon composites were fabricated from graphite nanoplatelets and pitch powders by a hot-pressing technology followed by carbonization and graphitization. The XRD and pole figure results show that the incorporation of pitch induces the decrease of size ( L a ) and orientation degree of graphitic crystallites, while the in-plane thermal conductivity of graphitized sample is increased with the increasing pitch content up to 6 wt.%, achieving a maximum value of 405 W/m K. The pitch binders are filled into the voids to bridge two or more graphite nanoplatelets particles together to form extra thermal paths, which makes a great contribution to the enhancement of thermal conductivity. A thermal conductivity model for the graphitized composites is constructed based on a bridging mechanism, and the predicted results fit well with the experimental results.